Deskripsi Pemahaman Konsep Kubus dan Balok Melalui Pembelajaran Daring - Ibrahim, Faisal; Ismail, Sumarno; Ismail, Yamin (Scimadly Publishing, 2024)
This study aims to describe students understanding of mathematical concepts through online learning for students of SMP Negeri 1 Suwawa regarding the concepts of cubes and cuboids. This research is descriptive with a quantitative approach. The subjects of this study were 35 students from classes VIII of SMP Negeri 1 Suwawa. The instrument used was essay questions. The research data were obtained from the results of the essay test. The results showed that the understanding of cubes and cuboids for class VIII was categorized as low for 28.57% of the students, medium for 63%, and high for 9%.